2021
DOI: 10.1371/journal.pone.0247565
|View full text |Cite
|
Sign up to set email alerts
|

Identification of success factors in elite wrestlers—An exploratory study

Abstract: Identification of success factors in wrestling as well as establishing their hierarchy are crucial from a cognitive and practical standpoint. It may provide a lot of practical recommendations related to wrestling-specific training. The aim of this study was to identify and establish the hierarchy of success factors in wrestling regardless of a fighting style and weight class. This study included 168 elite male freestyle and Greco-Roman wrestlers. They were divided into two groups: athletes who won medals (succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 39 publications
(71 reference statements)
0
26
1
1
Order By: Relevance
“…One of the characteristic features of achieving mastery in wresting is physical fitness. Many studies demonstrate a relationship between physical preparation and performance of wrestlers during competitions [10,11,12,13,14,15]. It is also indicated that physical fitness profiles of wrestlers differ depending on their wrestling style and sports class [10,16,17] and distinguish medal winners from competitors that do not achieve the highest sport results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the characteristic features of achieving mastery in wresting is physical fitness. Many studies demonstrate a relationship between physical preparation and performance of wrestlers during competitions [10,11,12,13,14,15]. It is also indicated that physical fitness profiles of wrestlers differ depending on their wrestling style and sports class [10,16,17] and distinguish medal winners from competitors that do not achieve the highest sport results.…”
Section: Introductionmentioning
confidence: 99%
“…Yoon [5] showed that in order to achieve the highest results in international competitions, wrestlers have to achieve excellent athleticism and physical fitness during training. According to one study [11], there are seven key factors that influence wrestlers' success. These include peak power of upper limb muscles, strength endurance (pull-ups), response time, special endurance (throws of the mannequin), wrestling-specific fitness (wrestling circle), special technical skills in a horizontal position (trunk grip gut wrench, reverse waistlock from a standing position).…”
Section: Introductionmentioning
confidence: 99%
“…Wrestling athletes need strength endurance when defending or attacking (Rahmani & Mirzaei, 2019), because if these components are weak, they will experience difficulties. Strength endurance is one of the factors to be successful in wrestling (Cieslinski et al, 2021), because it is good to support the training process or in matches and to be able to show the best performance (Pdate et al, 2017). In the competition itself, we know that athletes perform an attack or defend movements repeatedly with high intensity and pressure from the opponent, therefore athletes need to have Strength endurance to be able to display the best performance.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigate the physique and physical fitness profiles of wrestlers at various levels to investigate the physical and physiological differences that could contribute to the success of wrestlers [7,[11][12][13][14][15][16]. According to a previous study, wrestlers have a physique of strong shoulder girdles and arms with a long upper body, short lower extremities, and a low lower limb/trunk ratio [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of South Korea, which fosters wrestling as a major sport, it is indispensable to develop programs for predicting and training potential medalists to win medals in Greco-Roman wrestling. Many researchers have focused work on describing physical differences between elite and amateur wrestlers [16,25,27]. However, to the best of our knowledge, the factors that determine top-level performance amongst elite wrestlers have not been reported.…”
Section: Introductionmentioning
confidence: 99%